<span>4972.62319562
For future reference, you can just google something that simple!! :)</span>
Parabola form : (y-k) = a(x-h)², where h and k are the vertex(h , k)
The vertex is given (2 , - 9), the equation of the parabola becomes:
y+9 = a(x-2)²
But we know this curve passes through (5, - 18)
Plug the respective values of x & y in the equation:
-18 +9 = a(5-2)² → - 9 = 9a & a = -9/9 and a= - 1
Answer:
11
Step-by-step explanation:
Answer:
Its A.
Step-by-step explanation:
I just finsihed that question.